برامج الرسوم المتحركة وأثرها في الاكتساب اللغوي والتربوي لدى الطفل - دراسة تقويمية في نماذج من قناة CN في ضوء نظرية الغرس الثقافي - قمر لبيض (My University, 2023)
Abstract The current study aimed at monitoring the language, the behaviors and the values reflected in the contents of the cartoon programs of Cartoon Network in Arabic (CN in Arabic) and their impact on children through analyzing the content of five animation programs of different artistic genres, and then asking a set of questions to a sample of parents showing their attitude towards the habits and the behaviors of their children in watching CN in Arabic and the extent of their negligence, and the effect of the channel’s programs on their children. Finally linking the results to the analysis of the contents to attain the purpose of the research showed that the CN channel in Arabic forms a danger and a threat to the child, especially in the absence of family control, because he/she does not distinguish between the right and the wrong, and he/she considers all the actions presented to him/her as postulates that can be applied and practiced without taking into account his/her environment and society. ---------------------- الملخص: استهدفت الدراسة رصد اللغة و السلوكيات والقيم التي تعكسها مضامين برامج الرسوم المتحركة لقناة كرتون نتورك بالعربية( CN بالعربية) وتأثيرها على الأطفال من خلال تحليل محتوى خمسة برامج رسوم متحركة ذات أصناف فنيَّة مختلفة، ومن ثم طرح مجموعة أسئلة على عينة من الأولياء تبين موقفهم من عادات و أنماط مشاهدة أطفالهم لقناة CN بالعربية و مدى تغافلهم، وتأثير برامج القناة على أطفالهم ، ثم وربط النتائج مع تحليل المضامين لنصل في الأخير لهدف البحث، فقناة CN بالعربية تشكل خطر وتهديد على للطفل خاصة في غياب الرقابة الأسريَّة كونه لا يميز بين الصواب والخطأ ويعتبر كل التصرفات المعروضة أمامه مسلمات يمكن تطبيقها وممارستها دون مراعاة بيئته أو مجتمعه. ----------------- Résumé L'étude visait à surveiller le langage, les comportements et les valeurs reflétés dans le contenu des programmes de dessins animés de Cartoon Network en arabe (CN en arabe) et leur impact sur les enfants en analysant le contenu de cinq programmes d'animation de différents genres artistiques, puis poser une série de questions à un échantillon de parents pour montrer leur position sur les habitudes. Leurs enfants regardent CN en arabe et l'ampleur de leur négligence et l'impact des programmes de la chaîne sur leurs enfants, puis associent les résultats à l'analyse de contenu pour finalement atteindre l'objectif de la recherche Les postulats peuvent être appliqués et pratiqués sans prendre en compte son environnement ou sa société